EFFECTS ON RESIDENT SAFETY OF EFFORTS TO REDUCE HOSPITAL TRANSFERS. (11th November 2018) - Tappen, R; Newman, D; Huckfeldt, P; Engstrom, G; Wolf, D; Ouslander, J
Abstract: The Centers for Medicare and Medicaid (CMS) have incentivized the reduction of hospital transfers of nursing home residents. A number of studies have evaluated the effectiveness of efforts to reduce these transfers but the question of resident safety has not been previously addressed. The effects of implementation of the well-known INTERACT™ quality improvement program on resident safety indicators were examined in this secondary analysis of a randomized trial of the INTERACT™ program. Altogether, 264 nursing homes were randomized into intervention (INTERACT™ program implementation) and comparison groups. Data from the Minimum Data Set (MDS) and from nursing home report were used to evaluate resident safety. MDS data for rates of unintentional weight loss, malnutrition, hip fracture, pneumonia, wound infection, septicemia, urinary tract infection and falls with injury in the intervention year were compared with data from the previous year. Nursing home reports of unintentional weight loss, dehydration, rates of falls, pressure ulcers, severe pain and unexpected deaths were also collected from intervention facilities and compared across levels of INTERACT™ tool usage. No adverse effects on resident safety were found in the comparisons between intervention and control groups or in the high versus low use of the INTERACT™ tools in the intervention group with the exception of the lower rates of reported severe pain in the high use facilities. In this analysis, no evidence was found that resident safety was compromised when the INTERACT™ program was implemented.